Cassava/Yuca/Manioc - Keja Lys Valens (Humanities)
Cassava/Yuca/Manioc: This staple of Indigenous Caribbean diets has gone from being decried for its danger and denigrated for its supposed inferiority to wheat by the early colonists, to being among the few foods that nourished slaves, to creolizing into postcolonial national dishes, and to being touted as a wonder food resistant to the climate disaster and dietary breakdowns that manifest the slow violence of the colonial project. Is the uplifting of cassava the rise of the Caribbean plot, the next step in neocolonial globalist expropriation of things Caribbean, or something of both? This paper traces discourses of cassava from the writings of early colonialists like Pere Labat through Caribbean cookbooks of the independence era where it was creolized with African, European, and Asian techniques and traditions and into postcolonial diasporic food writing and commercial projects from Carmeta’s Bajan food independence through contemporary global agriculture projects promoting cassava. Cassava/Yuca/Manioc, this paper argues, continues to be deterritorialized on a global scale at the same time as, in the Caribbean, it continues to nourish locally grounded persistence, adaptation, resistance, and thriving.